FORMATION OF FUND OF ESTIMATED MEANS WHEN STUDYING NATIONAL HISTORY BY MEANS OF THE INFORMATIVE AND ACTIVE MATRIX - Tamara B. Tarabrina; Olga B. Voloshina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article the problem of measurability of knowledge and formation of competences of profes-sional education when studying discipline "History" is considered. The tests representing in-terconnected sequence of elements of a matrix which is defined not only algorithm and logic of the solution of educational tasks, but also dependence of receiving the correct answer on right performance previous are offered. It is shown that in modern education the essential role will be played by the personified training relying on sampling and measurability of the content of educational process. This article is dedicated to the inspection methods of self-depended students work in academy. Organization and inspection are impulse forces for learning process and acquirement. The Theory of supposed patterns for organization forming and for inspection of self-dependent students’ work is also set in this article